If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(u+3)=6u+19
We move all terms to the left:
6(u+3)-(6u+19)=0
We multiply parentheses
6u-(6u+19)+18=0
We get rid of parentheses
6u-6u-19+18=0
We add all the numbers together, and all the variables
-1!=0
There is no solution for this equation
| 295=85-v | | 5(r+9)=-3(1-r) | | 4.7w+3.72=3.4w-14.74 | | –8−8s=–10s | | 3x(8+16)/4= | | r-257=666 | | 9t-3=-7+7t | | 10+8w=9w | | r-257=66 | | (x-3)²-(3-x)²=1 | | 63=8y-52.8 | | 5(x+1)=-6 | | 6+2b=b | | 490-56=x6 | | t-378=603 | | (7x-2)=(4x+9)+(2x+6) | | 2.3n-13.8=-10.5n+9.16-3.6n | | h/18=21 | | -9k=-9-10k | | 7.50x-6.25=26.25 | | 434=6x | | 8+12u=10u | | 20+12p-18p=-10-3p | | h+1=100 | | 7x+2(4–2x)=-25+6 | | 7(v+6)=7v+12 | | -7+15k=13k-15 | | 8-7s=-8s-2 | | k+11=98 | | 6.25x-7.50=26.25 | | -3x-5-x+3=-2(2x+3) | | 17.5=17.4y-0.36 |